Chlorodifluoroacetyl Cyanide, ClF 2 CC(O)CN: Synthesis, Structure, and Spectroscopic Characterization - Ramos Guerrero, Luis Alejandro (2011)
The novel molecule difluorochloroacetyl cyanide, ClF2CC(O)CN, has been characterized by IR (gas phase, Ar matrix), Raman (liquid), 19F and 13C NMR, and photoelectron (PES) spectroscopies; photoionization mass spectrometry (PIMS); and gas electron diffraction (GED). The conformational properties of ClF2CC(O)CN have been studied by joint application of vibrational spectroscopy, GED, and quantum chemical calculations. The existence of two conformers is detected in the gas and liquid phases, in which the C Cl bond adopts gauche and syn orientations with respect to the CdO group. The computed enthalpy difference is in harmony with the experimental results of the gauche being more stable than the syn conformer by ΔH = 1.3 kcal mol 1 (MP2/ccpVTZ). The valence electronic properties and the possible ionization and dissociation processes of the title compound are studied using the PES and PIMS. The experimental first vertical ionization energy of 12.0 eV corresponds to the ejection of an electron of the oxygen lone pairs. Taking into account the properties and broad applications of acyl cyanides, ClF2CC(O)CN is a promising new precursor in preparative chemistry.